2020
DOI: 10.1177/1360780419895524
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Online or Offline? Patterns and Trends for Co-Resident Couples in Early 21st-Century Britain

Abstract: Data from the 2010–2012 National Survey of Sexual Attitudes and Lifestyles (NATSAL-3) are used to document trends and patterns in where co-resident couples in Britain first met, focusing specifically on the rapid rise of meeting online, which both echoes and differs from a corresponding US increase; in Britain, meeting online largely appears to have substituted for meetings in settings to which access is relatively unrestricted, for example, pubs and public places. While meeting online appears widespread acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Does a large and more easily accessible supply of potential partners, as well as an appeal to novel audiences [6], make dating apps a virtual social space more likely to encourage exogamy? Empirical studies have found that Internet-matched heterosexual unions display less within-couple similarity in terms of education, race or religious background [10,34], especially compared to unions created in typically homogenous settings, such as school, circles of friends, or family [35]. Most studies, however, were unable to single out the specific effect of dating websites or apps on exogamy, and largely focused on couples formed via the Internet in general [34], or through dating websites and apps jointly considered [10].…”
Section: Is Meeting Through Dating Apps Linked To More Exogamy?mentioning
confidence: 99%
“…Does a large and more easily accessible supply of potential partners, as well as an appeal to novel audiences [6], make dating apps a virtual social space more likely to encourage exogamy? Empirical studies have found that Internet-matched heterosexual unions display less within-couple similarity in terms of education, race or religious background [10,34], especially compared to unions created in typically homogenous settings, such as school, circles of friends, or family [35]. Most studies, however, were unable to single out the specific effect of dating websites or apps on exogamy, and largely focused on couples formed via the Internet in general [34], or through dating websites and apps jointly considered [10].…”
Section: Is Meeting Through Dating Apps Linked To More Exogamy?mentioning
confidence: 99%
“…In contemporary Western societies, the number of spouses meeting for the first time online has grown dramatically, siding (and in some cases surpassing) traditional meeting places such as school, work, neighborhood, and frienship (for a summary, see Lampard, 2020).…”
Section: Evidences Causes and Consequencesmentioning
confidence: 99%
“…The delayed marriage can result in the partner being found out of the educational system, which is one of the main marriage markets (Sabotka & Toulemon, 2008). The general shift toward a service economy also makes it possible to make use of marriage services carried out by professionals, who have also been able to reduce the social stigma associated with those who use them (Ahuvia & Adelman, 1992;Lampard, 2020). Using the Internet to find a partner has become a socially accepted practice (Smith & Duggan, 2013).…”
Section: Evidences Causes and Consequencesmentioning
confidence: 99%
See 2 more Smart Citations